PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT RELIFE PROPERTY JAKARTA SELATAN - Siti Nurhayati; Siska Yunanti (Journal of Research and Publication Innovation, 2025)
The purpose of the study was to determine the effect of work motivation discipline on employee performance at PT. Relife Property in Jakarta partially and simultaneously. The research method used is quantitative, with the nature of quantitative associative research. The population taken was 60 people. Data collection techniques using questionnaires (Questionnaires). Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing with the help of the Statistical Product and Service (SPSS) version 24 program. The results of the study showed partially. Discipline on employee performance partially has a significant positive effect which is indicated by This can be seen from the t count> t table (10.420> 1.978) and is also reinforced by the ρ value < sih.0.05 or 0.000 <0.05 and has a large influence contribution of 47.2% with a strong relationship level because it has a correlation value of 0.687. Work motivation has a significant effect on employee performance, this can be seen from the calculated F value> F table (79,415> 2,680) and is reinforced by the P value <sig 0.05 or 0.000 <0.05 and has a contribution of 61.6% and a very strong relationship level because it has a correlation value of 0.785 and a regression equation of Y = 2.988 + 0.359 X1 + 0.532 X.